b-Glucan Comparison in the Mushrooms of Medicinal Fungal Species - Totowiputro, Dicky Kurniawan; Sargowo, Djanggan; Tjokroprawiro, Askandar; Rifa'i, Muhaimin (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Agaricus blazei Murill has been known as a mushroom with medicinal properties, such as its efficacy in maintaining the immune system and other metabolic processes. The main polysaccharide found in A. blazei, is b-glucan. This study aims to quantify and compare b-glucan content in A. blazei compared with the medicinal mushrooms Ganoderma sp. and Pleurotus ostreatus. ?-glucan was extracted from each species using an alkaloid extraction method. The b-glucan content was determined using UV-Vis Spectrophotometer at a wavelength of 220 nm. The data showed that A. blazei contained the highest level of b-glucan, 6.99% (w/w), while the other mushrooms contained less than 2 %. This study obtained that A. blazei contain high levels of b-glucan compared with Ganoderma sp. and Pleurotus ostreatus. Thus, A. blazei has the potential as medicine, especially to maintain the balance of the immune system. To keep the body healthy and balance immune system patient can consume Agaricus blazei Muril.